The Melatonin Agonist Ramelteon Induces Duration-Dependent Clock Gene Expression through cAMP Signaling in Pancreatic INS-1 β-Cells - Nishiyama, Keiji (Public Library of Science, 2014)
Prolonged exposure to melatonin improves glycemic control in animals. Although glucose metabolism is controlled by circadian clock genes, little is known about the role of melatonin signaling and its duration in the regulation of clock gene expression in pancreatic β-cells. Activation of MT(1) and MT(2) melatonin receptors inhibits cAMP signaling, which mediates clock gene expression. Therefore, this study investigated exposure duration-dependent alterations in cAMP element-binding protein (CREB) phosphorylation and clock gene expression that occur during and after exposure to ramelteon, a selective melatonin agonist used to treat insomnia. In rat INS-1 cells, a pancreatic β-cell line endogenously expressing melatonin receptors, ramelteon persistently decreased CREB phosphorylation during the treatment period (2–14 h), whereas the subsequent washout induced an enhancement of forskolin-stimulated CREB phosphorylation in a duration- and concentration-dependent manner. This augmentation was blocked by forskolin or the melatonin receptor antagonist luzindole. Similarly, gene expression analyses of 7 clock genes revealed the duration dependency of the effects of ramelteon on Rev-erbα and Bmal1 expression through melatonin receptor-mediated cAMP signaling; longer exposure times (14 h) resulted in greater increases in the expression and signaling of Rev-erbα, which is related to β-cell functions. Interestingly, this led to amplified oscillatory Rev-erbα and Bmal1 expression after agonist washout and forskolin stimulation. These results provide new insights into the duration-dependent effects of ramelteon on clock gene expression in INS-1 cells and may improve the understanding of its effect in vivo. The applicability of these results to pancreatic islets awaits further investigation.